Fabrication of Graphene/Zinc Oxide Nano-Heterostructure for Hydrogen Sensing - Yang-Ming Lu (MDPI AG, 2021)
In this study, hydrogen (H2) and methane (CH4) were used as reactive gases, and chemical vapor deposition (CVD) was used to grow single-layer graphene on a copper foil substrate. The single-layer graphene obtained was transferred to a single-crystal silicon substrate by PMMA transfer technology for the subsequent growth of nano zinc oxide. The characteristics of CVD-deposited graphene were analyzed by a Raman spectrometer, an optical microscope, a four-point probe, and an ultraviolet/visible spectrometer. The sol–gel method was applied to prepare the zinc oxide seed layer film with the spin-coating method, with methanol, zinc acetate, and sodium hydroxide as the precursors for growing ZnO nanostructures. On top of the ZnO seed layer, a one-dimensional zinc oxide nanostructure was grown by a hydrothermal method at 95 °C, using a zinc nitrate and hexamethylenetetramine mixture solution. The characteristics of the nano zinc oxide were analyzed by scanning electron microscope(SEM),x-ray diffractometer(XRD), and Raman spectrometer. The obtained graphene/zinc oxide nano-heterostructure sensor has a sensitivity of 1.06 at a sensing temperature of 205 °C and a concentration of hydrogen as low as 5 ppm, with excellent sensing repeatability. The main reason for this is that the zinc oxide nanostructure has a large specific surface area, and many oxygen vacancy defects exist on its surface. In addition, the P–N heterojunction formed between the n-type zinc oxide and the p-type graphene also contributes to hydrogen sensing.